Beyond protein synthesis: the emerging role of arginine in poultry nutrition and host-microbe interactions - Fathima, Shahna; Al Hakeem, Walid Ghazi; Selvaraj, Ramesh K.; Shanmugasundaram, Revathi (Frontiers in Physiology, 2024)
Arginine is a functional amino acid essential for various physiological processes in poultry. The dietary essentiality of arginine in poultry stems from the absence of the enzyme carbamoyl phosphate synthase-I. The specific requirement for arginine in poultry varies based on several factors, such as age, dietary factors, and physiological status. Additionally, arginine absorption and utilization are also influenced by the presence of antagonists. However, dietary interventions can mitigate the effect of these factors affecting arginine utilization. In poultry, arginine is utilized by four enzymes, namely inducible nitric oxide synthase (iNOS), arginase, arginine decarboxylase (ADC), and arginine: glycine amidinotransferase (AGAT). The intermediates and products of arginine metabolism by these enzymes mediate the different physiological functions of arginine in poultry. The most studied function of arginine in humans, as well as poultry, is its role in immune response. Arginine exerts immunomodulatory functions primarily through the metabolites nitric oxide (NO), ornithine, citrulline, and polyamines, which take part in inflammation or the resolution of inflammation. These properties of arginine and arginine metabolites potentiate its use as a nutraceutical to prevent the incidence of enteric diseases in poultry. Furthermore, arginine is utilized by the poultry gut microbiota, the metabolites of which might have important implications for gut microbial composition, immune regulation, metabolism, and overall host health. This comprehensive review provides insights into the multifaceted roles of arginine and arginine metabolites in poultry nutrition and well-being, with particular emphasis on the potential of arginine in immune regulation and microbial homeostasis in poultry.